2018
DOI: 10.1093/annonc/mdx638
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of alternating treatment with EP2006, a filgrastim biosimilar, and reference filgrastim: a phase III, randomised, double-blind clinical study in the prevention of severe neutropenia in patients with breast cancer receiving myelosuppressive chemotherapy

Abstract: There were no clinically meaningful results regarding efficacy, safety or immunogenicity when switching from reference to biosimilar filgrastim/EP2006, or vice versa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 19 publications
1
14
0
1
Order By: Relevance
“…21 A phase III trial of 218 patients with breast cancer receiving myelosuppressive chemotherapy with TAC (docetaxel/doxorubicin/cyclophosphamide) showed no clinically meaningful differences in efficacy, safety, or immunogenicity between filgrastim and filgrastimsndz, even in patients who alternated between the 2 in subsequent chemotherapy cycles. 18 A recently published combined analysis of this and another phase III trial on the safety of filgrastim-sndz in patients with breast cancer concluded that filgrastim-sndz has a safety profile consistent with previous studies of reference filgrastim. 22 Several retrospective studies also report similar efficacy between filgrastim-sndz and filgrastim for prophylaxis of chemotherapy-induced neutropenia.…”
Section: Biosimilarssupporting
confidence: 68%
See 1 more Smart Citation
“…21 A phase III trial of 218 patients with breast cancer receiving myelosuppressive chemotherapy with TAC (docetaxel/doxorubicin/cyclophosphamide) showed no clinically meaningful differences in efficacy, safety, or immunogenicity between filgrastim and filgrastimsndz, even in patients who alternated between the 2 in subsequent chemotherapy cycles. 18 A recently published combined analysis of this and another phase III trial on the safety of filgrastim-sndz in patients with breast cancer concluded that filgrastim-sndz has a safety profile consistent with previous studies of reference filgrastim. 22 Several retrospective studies also report similar efficacy between filgrastim-sndz and filgrastim for prophylaxis of chemotherapy-induced neutropenia.…”
Section: Biosimilarssupporting
confidence: 68%
“…Although no biosimilars have been designated as interchangeable by the FDA, limited data suggest that patients can alternate between the biosimilar and the originator biologic without any clinically meaningful differences in efficacy or safety. 18 Another concern is the potential for product drift that may arise during the manufacturing process of biologics and biosimilars, which could result in differences in efficacy and safety over time. Continued postmarketing surveillance of all biologic products is necessary for long-term monitoring of these agents.…”
Section: Biosimilarsmentioning
confidence: 99%
“…In some states, even if interchangeability is designated (after interchangeability regulatory requirements are finalized), providers or pharmacists must notify patient recipients of substitution . One U.S. study with 109 patients with cancer identified no safety concerns when biosimilar and reference filgrastim were administered after alternative chemotherapy cycles . Larger switching studies have not been reported.…”
Section: Interchangeabilitymentioning
confidence: 99%
“…In this review, we discuss the clinical evidence for biosimilar filgrastim, including the phase III confirmatory studies assessing filgrastim as primary prophylaxis to reduce duration of chemotherapy-induced febrile neutropenia [1214]. Following approval, clinical experience and real-world evidence have demonstrated the safety and efficacy of biosimilar filgrastim in patients with different tumor types undergoing myelosuppressive chemotherapy and in both autologous and allogeneic stem cell mobilization and severe chronic neutropenia.…”
Section: Introductionmentioning
confidence: 99%